Effect of Intermittent Warming on the Quality and Lipid Metabolism of Blueberry (Vaccinium corymbosum L., cv. Duke) Fruit - Dai, Hongyu; Wang, Yajuan; Ji, Shujuan; Kong, Ximan; Zhang, Fan; Zhou, Xin; Zhou, Qian (Frontiers in Plant Science, 2021)
The change of lipid metabolism is a key point of blueberry fruit after refrigeration. This study was conducted to evaluate the effects of intermittent warming (IW) of ‘DuKe’ blueberry fruit on its shelf life at 20 ± 0.5 °C following 30 d of refrigeration. IW-treated fruit showed higher contents of phosphatidylcholine, linoleic acid and oleic acid but lower contents of phosphatidic acid and palmitic acid compared to controls. Protective effects on the cell membrane were also reflected as inhibition of the activity phospholipase D and lipoxygenase. The blueberry fruit showed a lower decay and pitting incidence with higher firmness than control. Interestingly, IW increased C-repeat binding transcription factor gene expression, which can induce the expression of genes related to hypothermia tolerance in plant cells at low temperature. These results indicate that IW can prevent damage to the membrane lipids which occurs by senescence at low temperature of blueberry fruit.